You are on page 1of 11

# GRC

MATH ENHANCEMENT CLASS

Albert Niangar MEC Submitted to: Mr. Bernabe

May 10, 2012

Percentage can be expressed in various ways.85  9% = . and Proportion Percent (%) comes from the Latin word “per centum”.24 0.28 = 28%  9.20 x 100% = 20% = 0. It is usually preceded by the words “of”.09  136% = 1. Rate (R) Refers to the number of hundredths taken. Ratio.010 x 100% = 1% = 1.125% = .0132 .78 Converting Decimal to Percent Example:  . Converting percent to Decimal Example:  85% = .2 = 5620%  .36  . and “as great as”.36% = = = = = 0.63 x 100% = 163% Percentage.Percentage. “per” means “for every” while “cent” means “hundred”.80 = 80%  . Base.35 x 100% = 35% = 0.23 = 923%  56.00125  78% = .07 0. or as a ratio. decimal. “as much”. “as large”.80 0. and Rate Base (B) Refers to that numbers of which a certain number of hundredths is taken.0936 Converting Fractions to Percent Example:      = 0. It is identifiable because it is usually in the form of a percent (%). It can be written as a fraction. Percentage (P) Refers to the quantitative portion of a whole basic formula: (P = B x R) . or a fraction. as a decimal.32% 7% 9.93 x 100% = 93% = 0.12 = 12% Converting Percent to Fraction Example:      24% 80% 1.

12x – 6y =6 4x – 12y = 22 12x – 6y = 6 4x – 12y = 22] -3 12x – 6y = 6 -12x + 36y = -66 30y = -60 30 30 Y= -2 If Y=-2. While they arise quite naturally when modelling many phenomena. then equation (1) is. 2x + 6y = 13 3x – 2y = 3 2x + 6y = 13 3x – 2y = 3] 3 . 12x – 6(-2) = 6 12x + 12 = 6 12x = 6-12 12x = -6 12 12 X = -1/2 3. consider equation (2) -6x + 6(4) = -2 -6x + 24 = -2 -6x = -2 -24 -6x = -26 -6 -6 x = 26/6 x = 13 2.Linear Equations Linear equations can have one or more variables. they are particularly useful since many non-linear equations may be reduced to linear equations by assuming that quantities of interest vary to only a small extent from some "background" state. Linear equations do not include exponents. Solving Linear Equations by Elimination Example: 1. 12x – 13y = 2 –6x + 6y = –2 12x – 13y = 2 -6x +6y = -2] 2 12x – 13y = 2 -12x + 12y = -4 -y = -4 -1 -1 Y=4 If Y=4. Linear equations occur with great regularity in applied mathematics.

2x + 3y = 5 3x + 3y = 10 2x + 3y = 5 3x + 3y = 10] -1 2x + 3y = 5 -3x -3y = -10 -x = -5 -1 -1 X=5 If X=5. 2x + 3y = 15 4x – 3y = 3 2x + 3y = 15 4x . 3x – 2y = 3 3(2) – 2y = 3 6 – 2y = 3 -2y = 3-6 -2y = -3 -2 -2 Y = 2/3 4. then equation (2) is. then equation (1) is.2x + 6y = 13 9x – 6y = 9 11x = 22 11x = 22 11 11 X=2 If X=2. 4x – 3y = 3 4(3) – 3y = 3 12 – 3y = 3 -3y = 3-12 -3y = -9 -3 -3 Y=3 5. then equation (2) is. 2x + 3y = 5 2(5) +3y = 5 10 + 3y = 5 3y = 5-10 3y = -5 3 3 Y= .3y = 3] 1 2x + 3y = 15 4x – 3y = 3 6x = 18 6 6 X=3 If X=3.

2x – 3y = –2 4x + y = 24 Solve for the temporary Y Considering the second equation: 4x + y = 24 y = –4x + 24 substitute the temporary Y to the first equation: 2x – 3(–4x + 24) = –2 2x + 12x – 72 = –2 14x = 70 x=5 Plug this x-value back into either equation. and solve for the Y.Solving Linear Equations by Substitution Example: 1. X – Y = 3 X=3+Y Substitute the Value of X in this Equation: 2x-3y=5 2(3+y) -3y=5 6+2y-3y=5 6-y=5 1=y Y=1 Substitute the value of Y to the previous equation: X-Y=3 x-1=3 x=4+1 X=4 2. it will be simplest to just plug into this: y = –4(5) + 24 = -20 + 24 =4 {X = 5. Y = 4} 3. 3x+3 10 =10 3 3x= 10-10 X= 0 -6y +9y = 30-20 3 3 Y= 10 3 . since I already have an expression for "y =". 3x+3y=10 2x+3y=10 X=? x= -3y+10 3 Solve for Y. 2 -3y+10 +3y=10 3 -6y+20 +3y = 10 3 Solve for X.

3x+ 3(0)=10 3x=10 x = 10 3 2x – y = 7 2(8 – y) – y = 7 (16 – 2y) – y = 7 -3y = -9 -3 -3 Y=3 Substitute the value of Y and solve for X X+Y=8 X+3=8 X=5 Quadratic Equation Is one unknown X has the form Methods of solving Quadratic Equations  Factoring  Completing the Square  Quadratic Formula Factoring 1.y Solve for X. and c are real numbers and a 0. x + 5x + 6 = 0 2 x + 5x + 6 = (x + 2)(x + 3) (x + 2)(x + 3) = 0 x + 2 = 0 or x + 3 = 0 x = –2 or x = – 3 2 where a.4. X+Y=8 2x – y = 7 x + y =8 solve for the X x = 8. 3x+3y=10 3 3y+5 +3y=10 2 9y+15+3y=10 2 9y+6y = 20-15 2 2 15 Y= 15 2 2 Y=0 5. . b. 2x+3y=5 3x+3y=10 X=? x= -3y+5 2 Solve for Y.

x – 3 = 2x 2 x – 3 = 2x 2 x – 2x – 3 = 0 (x – 3)(x + 1) = 0 x – 3 = 0 or x + 1 = 0 x = 3 or x = –1 (x + 2)(x + 3) = 12 (x + 2)(x + 3) = 12 2 x + 5x + 6 = 12 2 x + 5x – 6 = 0 (x + 6)(x – 1) = 0 x + 6 = 0 or x – 1 = 0 x = –6 or x = 1 x – 5x = 0 x(x – 5) = 0 x = 0 or x – 5 = 0 x = 0 or x = 5 x –4=0 2 x –4=0 (x – 2)(x + 2) = 0 x – 2 = 0 or x + 2 = 0 x = 2 or x = –2 2 2 2 3.) ½(6) =6/2 =3 √ = 55 +9 √ =√ . Completing the Square 1. 4. 5.) ½(-8) = -8/2 = -4 = 16 √ (x-4)= ± 7 X= ± 7 + 4 X=11 X= -3 2.2.

) ½(2) =2/2 =1 = 15 +1 √ =√ X=±4 – 1 X= 4-1 X=3 x= -4-1 x= -5 4.X=±8 – 3 X= 8-3 X=5 x= -8-3 x= -11 3.) ½(3) =3/2 = 10 +9/4 √ =√ X=±7/2 – 3/2 X= 7/2-3/2 X=4/2 X=2 x= -7/2-3/2 x= -10/2 X= 5 .

6x2 + 11x – 35 = 0 √ √ 3. √ √ √ √ . √ √ √ √ √ √ √ 2.5.) ½(-4) =-4/2 =-2 = 21 +4 √ =√ X=±5 + 2 X= 5+2 X=37 x= -5+2 x= -3 Quadratic Formula 1.

It is obtained by subtracting the product of the entries on the secondary (ascending) diagonal from the lower left to the upper right from the product of the entries on the principal (descending) diagonal from the upper left to the lower left. The number of (horizontal) rows and the number of (vertical) columns of entries in the representation of a determinant. B1 and B2 are called the entries (or elements) of the determinant. B1. | Example: 1. | Ascending or secondary diagonal Descending or Principal Diagonal D= = 24+3+42-42-4-18 =5 Dx = = 24+24+56-336-4-24 = -260 Dy = = 16+2+168-28-16-12 = 130 Dz = = 96+12+12-12-16-72 = 20 Dx= . A2. The value of the determinant of order two is defined as A1. determine its dimensions. B2 – A2.is a square array of numerals enclosed by vertical bars such as | | The numbers A1.Solving Systems of Linear Equations using determinants Determinant .

2. D= = -8 + (-18) + (-12) – 16 – (-9) – 12 = -57 Dx = = -16 + (-72) + (-12) – 64 – (-18) – 12 = -158 Dy = = -4+12+32-8-24-(-8) = 16 Dz = = 16+ (-6) + (-6)-8-(-3)-(-24) = 23 .